2016
DOI: 10.3389/fmicb.2016.00332
|View full text |Cite
|
Sign up to set email alerts
|

Piriformospora indica: Potential and Significance in Plant Stress Tolerance

Abstract: Owing to its exceptional ability to efficiently promote plant growth, protection and stress tolerance, a mycorrhiza like endophytic Agaricomycetes fungus Piriformospora indica has received a great attention over the last few decades. P. indica is an axenically cultiviable fungus which exhibits its versatility for colonizing/hosting a broad range of plant species through directly manipulating plant hormone-signaling pathway during the course of mutualism. P. indica-root colonization leads to a better plant perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
114
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(133 citation statements)
references
References 155 publications
(344 reference statements)
6
114
0
1
Order By: Relevance
“…Mutualistic symbiotic relationships are well known in arbuscular mycorrhiza as well as in several other types of root‐inhabiting fungi (van der Heijden et al ., ; Weiß et al ., ). Fungal species belonging to these groups have a wide range of proven beneficial functions including enhancement of growth, nutrient and water uptake and stress tolerance and pest resistance (Bonfante and Genre, ; Baum et al ., ; Gill et al ., ). Similar beneficial functions are known in EpichloĂ« endophytes, which are a group of sexual ( EpichloĂ« spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Mutualistic symbiotic relationships are well known in arbuscular mycorrhiza as well as in several other types of root‐inhabiting fungi (van der Heijden et al ., ; Weiß et al ., ). Fungal species belonging to these groups have a wide range of proven beneficial functions including enhancement of growth, nutrient and water uptake and stress tolerance and pest resistance (Bonfante and Genre, ; Baum et al ., ; Gill et al ., ). Similar beneficial functions are known in EpichloĂ« endophytes, which are a group of sexual ( EpichloĂ« spp.)…”
Section: Introductionmentioning
confidence: 99%
“…and biotic (volatile organic compounds, amino acids, hormones, enzymes, phenolics, etc.) signals (OrtĂ­z-Castro et al 2009;Gill et al 2016;Zhu 2016), with synergistic and (or) competing effects (Oldroyd 2013). Recent results on the regulation of seed dormancy show that important biotic seed germination signals lay in mycovitality and bactovitality, which refer to a form of fungal and bacterial endosymbiosis, respectively, using different endophytic strains with a variety of activities (Vujanovic and Germida 2013).…”
Section: Mycovitality: Improving Dormancy Release and Germinationmentioning
confidence: 99%
“…Biostratification is the exposure of seeds to beneficial microbial [fungal and (or) bacterial] partners that create conditions conductive to breaking dormancy and enhancing germination, whereas biopriming involves combined physical (hydration-dehydration) and microbial pretreatments to activate seed metabolism. The fungal inoculants were involved in transcriptional regulation (Chacon et al 2007;Zuccaro et al 2011;Sarkar and Reinhold-hurek 2014;Gill et al 2016) as well as epigenetic modification of chromatin structure and methylation, and appear capable of shaping the profile of transposon/retrotransposon elements that mediate cell function and phenotypic variation in plants ( PankeBuisse et al 2014). Hubbard et al (2014a) found that the abundance of CACTA, Gypsy, Copia, and cytochrome p450 transposable elements coincides with the altered DNA methylation in drought-stressed wheat seedlings.…”
Section: Mycovitality: Improving Dormancy Release and Germinationmentioning
confidence: 99%
“…Piriformospora indica is a root endophytic fungus, originally isolated from the Thar Desert in India [13]. It interacts beneficially with a broad spectrum of plants and is known to enhance plant growth, biomass production, drought tolerance, salt tolerance, phosphorus acquisition, and resistance to pathogens [14,15]. In fact, P. indica is functionally similar to arbuscular mycorrhiza fungi (AMF) except that it can grow axenically.…”
Section: Introductionmentioning
confidence: 99%